2015
DOI: 10.5539/jas.v7n10p239
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Some Feed Additives against Dizocelpine Induced Oxidative Stress in Testes of Rabbit Bucks

Abstract: As optimization of farm animals reproductive performance is a main objective, the present study was, undertaken to investigate the possible protective effect of vitamin C, vitamin E and olive pomace against dizocilpine (MK-801) induced oxidative stress and its resultant alterations on antioxidant status, spermiogram, hormonal, enzyme markers and histomorphology of testes of rabbit bucks during first and second month of the experiment. For this purpose thirty six male New Zealand White rabbits bucks were equall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…In line with our previous results, the experiments showed that the administration of MK-801 to rat testis resulted in increased oxidative stress in rat testis [43]. Similarly, Saleh et al demonstrated that the administration of MK-801 to rabbits increased the atrophy of the tubular structure and the degeneration of germinal cells in the lumen of the seminiferous tubule in histopathological evaluation [44]. Moreover, it was reported that the level of total antioxidant status and sperm kinematics parameters have decreased following the administration of MK-801 [45,46].…”
Section: Discussionsupporting
confidence: 87%
“…In line with our previous results, the experiments showed that the administration of MK-801 to rat testis resulted in increased oxidative stress in rat testis [43]. Similarly, Saleh et al demonstrated that the administration of MK-801 to rabbits increased the atrophy of the tubular structure and the degeneration of germinal cells in the lumen of the seminiferous tubule in histopathological evaluation [44]. Moreover, it was reported that the level of total antioxidant status and sperm kinematics parameters have decreased following the administration of MK-801 [45,46].…”
Section: Discussionsupporting
confidence: 87%
“…In another study on the rabbit bucks, MK-801 injection was caused a significant decrease in sperm number, antioxidant parameters and pathological changes in testis. Dietary supplementation of vitamin E, vitamin C, and olive pomace ameliorated the related parameters in the testis (19). In the present study, the emerged oxidative stress sourced by the MK-801 decreased the testicular weight same as previous studies (14,16).…”
Section: Discussionsupporting
confidence: 86%
“…The control group (C) was fed the control diet. The other three groups of rabbits comprised the treatment groups: group P, supplemented with 4.5% pomegranate peel in their diet (Zeweil, & Elgindy, 2016); group O, supplemented with 10% olive pomace in their diet (Saleh et al, 2015); and group PO, supplemented with a mixture of pomegranate peel and olive pomace. After the end of the one‐month adaption period, the does were randomly selected and used for the experiments.…”
Section: Methodsmentioning
confidence: 99%